2016
DOI: 10.1515/pomr-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Motion Prediction of Catamaran with a Semisubmersible Bow in Wave

Abstract: Compared with standard vessels, a slender catamaran with a semi-submerged bow (SSB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…The rigid motion approach causes difficulties for free surface refinement, especially in pitch, and deforming meshes may lead to cell quality problems. The authors of [23] showed that the overset grid method was more accurate in the prediction of the motion response of an SSB catamaran under regular wave conditions when heading in the wave. The overset region moves with the hull over a static background region.…”
Section: Fig 5 the Dimensions Of The Computational Domainmentioning
confidence: 99%
“…The rigid motion approach causes difficulties for free surface refinement, especially in pitch, and deforming meshes may lead to cell quality problems. The authors of [23] showed that the overset grid method was more accurate in the prediction of the motion response of an SSB catamaran under regular wave conditions when heading in the wave. The overset region moves with the hull over a static background region.…”
Section: Fig 5 the Dimensions Of The Computational Domainmentioning
confidence: 99%
“…They pointed out that the RANS method gave higher accuracy compared other numerical calculations based on potential theory when accounting for the contribution of the stabilizing fins. Sun et al [17] calculated the seakeeping performance of a catamaran with a semi-submerged bow (SSB) in model scale adopting overset grid and motion region methods. Comparisons among available experimental data and numerical results illustrated that overset grid technology was more accurate than the motion region technology when calculating large ship motions.…”
Section: Introductionmentioning
confidence: 99%
“…Following the works of [12][13][14][15][16], the numerical methods are adopted to solve and analyze the fluid problem. The computational fluid dynamics (CFD) simulation are the best alternative with several advantages such as allow to simulate using actual and model geometry scale in extreme condition of the fluid flow and the CFD simulation also have a good agreement with experimental data [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%